Querying the Queer: A Study of the Queer Identity in the Sri Lankan English Novel - Siriwardena, D (University of Sri Jayawardenepura, 2017)
Employing the insights gleaned from queer theory, this paper engages with the literary representation of tabooed sexualities by scrutinizing the depiction of the queer character in the post- Independence Sri Lankan novel. The methodology of the study is based on a textual examination. The primary texts under scrutiny are three texts by the two pioneers of the Sri Lankan English novel, Punyakanthi Wijenaike (Giraya and Amulet) and James Goonewardena (An Asian Gambit); in which one finds the earliest appearance of the queer character in Sri Lankan English fiction. In a nutshell, the paper examines how these authors negotiate with what the feminist critics term, “the perceptual screen provided by our patriarchal cultural conditioning” by attempting to see if the works of these authors hold any subversive potential. This end is achieved by examining whether the depiction of the queer character in the novels of these authors is employed as a means of tracing a redefinition or a reaffirmation of the patriarchal social institutions such as love and family. In the exploration it becomes evident that especially in Wijenaike’s work there is a critical recognition the discriminatory aspects of certain patriarchal institutions. Nevertheless, the study unearths that in spite of the authors’ ostensibly radical move of engaging with tabooed sexualities in the Sri Lankan society in their novels, their depiction of the queer character is predominantly governed by homophobic, heterosexist undercurrents. It is hoped that this paper will throw new light on the preoccupations of the Sri Lankan English writers, enable new readings of old texts, and illuminate a previously unexplored area of experience in Sri Lankan English fiction.